Epidemiología del fracaso renal agudo en las UCI españolas. Estudio prospectivo multicéntrico FRAMI. - Herrera-Gutiérrez, Manuel Enrique; Seller Pérez, Gemma Luisa; Maynar Moliner, Javier; Sánchez Izquierdo Riera, José Ángel (Elsevier, 2006)
Objective: Multicenter study oriented at establishing the incidence and prognosis of acute kidney failure (AKF) in the ICU of our country. Material and methods: Prospective study of adult patients admitted over 8 months in 43 Spanish ICUs to detect AKF defined as creatinine>or=2 mg/dl or diuresis<400 ml/24 hours (in chronic patients 100% increase of creatinine, excluding those with baseline creatinine>or=4 mg/dl). Results: 901 episodes of AKF (AKF episodes (incidence 5.7%), 55% of which occurred on admission. A total of 38.4% of the episodes were due to acute tubular necrosis (ATN), 36.6% to prerenal, and 21.2% to mixed. Renal depuration (RC) was required in 38%. Mortality was 42.3% during the AKF episode (34.1% in those who were admitted with AKF versus 50.9% in those who developed it after admission), 80% in patients with Hepatorenal Syndrome, 51.6% in ATN and 29.9% in prerenal. We detect an independent relationship with mortality for age (OR 1.03), background of diabetes (OR 2.06), development of AKF in the ICU (OR 2.51), oliguria (OR 5.76) and RC (OR 2.32). Recovery of the kidney function occurred in 85.6% of the survivors and RC was maintained in only 1.1% on discharge from the ICU. We calculated the area under the curve of APACHE II on admission (0.62), SOFA on onset of AKF (0.68), Liaño index (0.7) and maximum SOFA (0.79). Conclusions: AKF in ICU patients does not show an elevated incidence but does have high mortality, presenting greater seriousness when it appears after admission. However, recovery is elevated in patients who survive. The usual prognostic indexes are not exact in this patient group, the ISA and maximum SOFA being those which shows a closer relationship with mortality.
https://openpolicyfinder.jisc.ac.uk/id/publication/4878
Keywords: Riñones - Enfermedades; Enfermedades - Epidemiología; Unidades de cuidados intensivos; Acute Kidney Injury / epidemiology; Intensive Care Units